Study of Flood Waves Resulting from Rain Precipitation with a Probability of Repeating 20-50 Years in Gamga River - الخضر, بسام; عمار, غطفان; احمد, علي (Latakia University Journal -Engineering Sciences Series, 2022)
Flood waves are one of the most important component which affect on River systems and the surrounding environment. The various studies aimed to investing these resources, and achieving a balance between the flow system and the protection of the stream and the maximum use of water source for various purposes. This research aim to Study of flood waves resulting from rain precipitation with a probability of repeating 20-50 years in Gamga River, Which was based on the altitude layer taken from the Japanese satellite ALOS (Advanced Land Observation Satellite), to obtain the topographical nature of the studied river, It was processed within G.I.S environment using the HEC-GEORAS tool, Were the Geometric data for the stream was prepared from cross-section, a central channel and banks of the flow…., and exported to the hydraulic modeling program HEC-RAS, Were the required hydraulic data has been entered. The results showed a significant change of the studied river when the resulting flood waves pass with potentials (20-50) years, Within the different section and its location and the diversity and importance of in-depth study and analysis, in order to achieve the maximum benefit from the stream while achieving the stability of the stream and protecting it from sudden changes.